2021
DOI: 10.1136/bmjopen-2020-047376
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Aging Research Group (CARG) score in older adults undergoing curative intent chemotherapy: a prospective cohort study

Abstract: ImportanceThe Cancer Aging Research Group (CARG) toxicity score is used to assess toxicity risk in geriatric patients receiving chemotherapy.ObjectiveThe primary aim was to validate the CARG score in geriatric patients treated with curative intent chemotherapy in predicting grade 3–5 toxicities.DesignThis was a longitudinal prospective observational study.SettingTata Memorial Hospital, Mumbai, India, a tertiary cancer care referral centre.ParticipantsPatients, aged ≥65 years, with gastrointestinal, breast or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…No elderly-specific trials of adjuvant chemotherapy in NSCLC have been conducted so far and a specific standardized tool for risk assessment in older patients undergoing adjuvant treatment after surgical resection is still lacking [ 21 ]. Only recently the Cancer Aging Research Group (CARG) score, which predicts grade 3–5 chemotherapy toxicity in older adults aged 65 years or older [ 22 ], has been validated in the adjuvant and neoadjuvant setting [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…No elderly-specific trials of adjuvant chemotherapy in NSCLC have been conducted so far and a specific standardized tool for risk assessment in older patients undergoing adjuvant treatment after surgical resection is still lacking [ 21 ]. Only recently the Cancer Aging Research Group (CARG) score, which predicts grade 3–5 chemotherapy toxicity in older adults aged 65 years or older [ 22 ], has been validated in the adjuvant and neoadjuvant setting [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable to those of the CARG toxicity tool development and validation cohort. 26,44 Of interest, the risk of chemotherapy-related toxic effects in patients with gastrointestinal or genitourinary cancers was reduced in our study. This finding differs from the original CARG developmental cohort, in which gastrointestinal or genitourinary cancers predicted an increased risk of chemotherapy-related toxic effects.…”
Section: Jama Network Open | Oncologymentioning
confidence: 73%
“…Other studies have evaluated the utility of the CARG model outside the US. [44][45][46] Within the continent of Asia, Ostwal et al 44 have validated the utility of the CARG model in the Indian population. Suto et al 45 have similarly found that the CARG model predicted chemotherapy-related toxic effects in a small (<100 patients) retrospective study conducted in a Japanese population, whereas a prospective validation study 46 of the CARG performed in Hong Kong had negative results, which may be attributed to the inclusion of patients who received only targeted therapy and no chemotherapy in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that validated measures of frailty are an important metric in assessing the benefit of a therapeutic intervention in the elderly population. The Geriatric Assessment has been successfully embedded within cooperative group clinical trials ( 34 ), and the Cancer in Aging Research Group Toxicity Score can identify subsets of older adults at higher risk of symptomatic adverse events or death ( 35 ). Clinical trial endpoints should include those outcomes that mirror the values and preferences of older adults ( 33 , 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%